2008
DOI: 10.1002/ijc.23939
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell secretion of chemokines during differentiation into osteoblasts, and their potential role in mediating interactions with breast cancer cells

Abstract: Over 70% of patients with advanced breast cancer will develop bone metastases for which there is no cure. Mesenchymal Stem Cells (MSCs) and their derivative osteoblasts are subpopulations of cells within the bone marrow environment, postulated as potential interacting targets for disseminating cancer cells because of their ability to secrete a range of chemokines. This study aimed to investigate chemokine secretion throughout MSC differentiation into osteoblasts and their effect on the breast cancer cells. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 49 publications
(66 reference statements)
3
84
0
4
Order By: Relevance
“…Reports from this laboratory and others have shown a significant increase in migration of breast cancer cells in response to factors secreted by MSCs [25,26], and this was reflected by increased expression of migratory genes seen here including MMP11 and CXCL12 [27]. Oncogenes and proto-oncogenes were upregulated both in a cell specific manner and, in the case of FOS and JUN, across all breast cancer cells retrieved following co-culture with MSCs.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Reports from this laboratory and others have shown a significant increase in migration of breast cancer cells in response to factors secreted by MSCs [25,26], and this was reflected by increased expression of migratory genes seen here including MMP11 and CXCL12 [27]. Oncogenes and proto-oncogenes were upregulated both in a cell specific manner and, in the case of FOS and JUN, across all breast cancer cells retrieved following co-culture with MSCs.…”
Section: Discussionsupporting
confidence: 53%
“…This tumor homing ability has prompted researchers to analyse MSCs as possible vectors for the targeted delivery of anti-cancer agents to tumor microenvironments [13]. However evidence suggests that interactions between MSCs and breast cancer cells may impact upon the phenotype of the cancer cell and promote their metastatic potential [7][8][9][14][15][16]. Understanding these interactions has become fundamental to determining whether the homing ability of MSCs should be harnessed for delivery of therapeutic agents or whether the MSC-tumour interactions should be considered a target for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are frequently recruited to the site of tissue injury or tumor growth and sometimes, in the appropriate and permissive environment and under stress conditions, this could also represent a potential source of malignancy. Thus, MSCs within the tumor stroma facilitate breast cancer metastasis through the secretion of the chemokines CCL5 [89] and CCL2 [90]. Likewise, hMSCs target osteosarcoma and promote its growth and pulmonary metastasis through secretion of CCL5 [91].…”
Section: Mscs and Tumor Growthmentioning
confidence: 99%
“…7,8 It was also shown that CAFs support the malignant properties of cancer spreading by secreting soluble factors such as pro-angiogenic factors, matrix metalloproteinases (MMPs), cytokines as well as chemokines and growth factors. 9 Among these cytokines, CCL2 and CCL5, which are known inflammatory mediators, were demonstrated to play important role in the mediation of the interaction between CAFs and breast cancer cells beyond SDF-1 [10][11][12][13] Dovitinib (formerly CHIR-258, TKI-258, Novartis pharmaceuticals) is an investigational new inhibitor of multiple tyrosine kinases that has in vitro inhibitory activity against basic fibroblast growth factor receptor (bFGFR), platelet-derived growth factor receptor (PDGFR), and vascular endothelial growth factor receptor (VEGFR) kinases with IC 50 values of approximately 10 nM. Further in vivo and in vitro data indicate that this drug blocked PDGFR/FGFR/VEGFR signaling in advanced melanoma, 4 pancreatic cancer, 14 breast carcinoma, 15 urothelial carcinoma, 16 impaired tumor growth, angiogenesis, and metastasis by effects on tumor cells, endothelial cells, and pericytes in vitro.…”
Section: Introductionmentioning
confidence: 99%